SiO2-PVA-Fe(acac)3 Hybrid Based Superparamagnetic Nanocomposites for Nanomedicine: Morpho-textural Evaluation and In Vitro Cytotoxicity Assay - Ana-Maria Putz; Cătălin Ianăși; Zoltán Dudás; Dorina Coricovac; Claudia (Farcas) Watz; Adél Len; László Almásy; Liviu Sacarescu; Cristina Dehelean (Molecules, 2020)
A facile sol-gel route has been applied to synthesize hybrid silica-PVA-iron oxide nanocomposite materials. A step-by-step calcination (processing temperatures up to 400 °C) was applied in order to oxidize the organics together with the iron precursor. Transmission electron microscopy, X-ray diffraction, small angle neutron scattering, and nitrogen porosimetry were used to determine the temperature-induced morpho-textural modifications. In vitro cytotoxicity assay was conducted by monitoring the cell viability by the means of MTT assay to qualify the materials as MRI contrast agents or as drug carriers. Two cell lines were considered: the HaCaT (human keratinocyte cell line) and the A375 tumour cell line of human melanoma. Five concentrations of 10 µg/mL, 30 µg/mL, 50 µg/mL, 100 µg/mL, and 200 µg/mL were tested, while using DMSO (dimethylsulfoxid) and PBS (phosphate saline buffer) as solvents. The HaCaT and A375 cell lines were exposed to the prepared agent suspensions for 24 h. In the case of DMSO (dimethyl sulfoxide) suspensions, the effect on human keratinocytes migration and proliferation were also evaluated. The results indicate that only the concentrations of 100 μg/mL and 200 μg/mL of the nanocomposite in DMSO induced a slight decrease in the HaCaT cell viability. The PBS based in vitro assay showed that the nanocomposite did not present toxicity on the HaCaT cells, even at high doses (200 μg/mL agent).